Totally visible transparent chloro-sulphide glasses based on Ga2S3-GeS2-CsCI - Ledemi, Y. [UNESP]; Calvez, L.; Roze, M.; Zhang, X. H.; Bureau, B.; Poulain, M.; Messaddeq, Younes [UNESP] (Natl Inst Optoelectronics, 2007)
In this paper, the influence on optical properties of alkali halides such as CsCl in a covalent glassy matrix has been investigated. Chalcogenide glasses belonging to the (GeS2)-(Ga2S3)-CsCI system with high ratio of CsCl present an entire transparency in the visible range. These glasses maintain good transmission up to 12 mu m. Furthermore, the thermo-mechanical properties and the glass hygroscopicity have been investigated as function of the CsCl amount. This new generation of glasses presents a great interest for optical application. They could be used both for passive applications (multi-spectral imaging) and active applications for rare-earth doping due to their good transmission in the visible range, increasing optical pumping possibilities.
Keywords: chalcogenide; halide; glass; visible transmission